2020
DOI: 10.1111/1750-3841.15419
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene protects neuroblastoma cells against oxidative damage via depression of ER stress

Abstract: Lycopene is a pigment derived from tomatoes and other red fruits, and has potent antioxidant and antitumor effects. However, its potential role in alleviating oxidative damage in neuronal cells is not well defined. In this study, we investigated the effects of lycopene on H 2 O 2-induced damage in neuroblastoma cells, as well as the underlying mechanisms. Exposure to H 2 O 2 markedly decreased the viability of SH-SY5Y cells and increased LDH release, both of which were reversed by lycopene pretreatment. Lycope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 69 publications
1
5
0
Order By: Relevance
“…We also found that addition of PE down-regulated gene expression related to UPR pathway, leading to relieve ER stress. The result was consistence with the previous study that inhibiting the PERK-CHOP signaling pathway to protect cells from ER stress-induced damage (48). Moreover, PE supplementation could inhibit inflammation induced by PA treatment.…”
Section: Discussionsupporting
confidence: 89%
“…We also found that addition of PE down-regulated gene expression related to UPR pathway, leading to relieve ER stress. The result was consistence with the previous study that inhibiting the PERK-CHOP signaling pathway to protect cells from ER stress-induced damage (48). Moreover, PE supplementation could inhibit inflammation induced by PA treatment.…”
Section: Discussionsupporting
confidence: 89%
“…For example, several experimental models have demonstrated the anti-oxidative effects of lycopene in both the peripheral and central nervous systems [8][9][10] . Our previous studies proved that lycopene shielded SH-SY5Y cells against oxidative toxicity through decreased endoplasmic reticulum stress [11] . The antineuroin ammatory effect of lycopene has been demonstrated in primary cultured rodent microglia [12,13] .…”
Section: Introductionmentioning
confidence: 89%
“…Cell viability is quantitative colorimetric assay to measure the mitochondrial activity of living cells (Ou et al, 2020). Briefly, the cells are observed to reach the 70% confluency, and cells were treated with various concentration (25, 50, 100, 150, 200, and 250 µM) of Fb1 for 24 h at 37 • C. On the other hand, to examine the protective effect of AP against Fb1, the cells were pretreated with AP at different concentrations (25, 50, and 100 µg).…”
Section: Mtt Assaymentioning
confidence: 99%